JOB SATISFACTION IN PERFORMANCE IMPROVEMENT - Indra Sintanta Sembiring; Kiki Farida Ferine; Sri Rahayu (International Conference on Health Science, Green Economics, Educational Review and Technology, 2025)
This study aims to examine the influence of training and team collaboration on job performance with job satisfaction as a mediating variable among employees at PT. PLN (Persero) UP3 North Medan. The research problem is based on the importance of human resources with high job performance to support organizational goals. However, in practice, there are inconsistencies between the implementation of training and team collaboration with the levels of job satisfaction and employee performance. The population of this study consisted of all employees at PT. PLN (Persero) UP3 Medan Utara, totaling 144 individuals. Since the population was less than 200, a census sampling technique (saturated sampling) was used, in which the entire population was included as the sample. The data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with the help of SmartPLS software. The results show that: (1) training has a positive and significant effect on job performance but does not significantly affect job satisfaction; (2) team collaboration has a positive and significant effect on both job satisfaction and job performance; (3) job satisfaction has a positive and significant effect on job performance; (4) job satisfaction significantly mediates the effect of team collaboration on job performance but does not significantly mediate the relationship between training and job performance. The study concludes that team collaboration is a crucial factor in enhancing both job satisfaction and performance, while the effectiveness of training should be re-evaluated to optimize its impact on employee satisfaction.